Healthcare Workers’ Perspectives on the Barriers to Providing HIV Services to Children in Sub-Saharan Africa - Chipo Mutambo; Khumbulani Hlongwana (AIDS Research and Treatment)
Background. In order to accelerate the HIV response to meet the UNAIDS 90-90-90 indicators for children, healthcare workers need to lead a scale-up of HIV services in primary healthcare settings. Such a scale-up will require investigation into existing barriers that prevent healthcare workers from effectively providing those services to children. Furthermore, if the identified barriers are not well understood, designing context-specific and effective public health response programmes may prove difficult. Objective. This study reviews the current literature pertaining to healthcare workers' perspectives on the barriers to providing HIV services to children in the primary care setting in Sub-Saharan Africa. Methods. English articles published between 2010 and April 2018 were searched in electronic databases including Sabinet, MEDLINE, PubMed, and Google Scholar. Key search words used during the search were “healthcare workers’ perspectives” and “barriers to providing HIV testing to children” OR “barriers to ART adherence AND children” and “barriers to HIV disclosure AND children.” Results. There are various barriers to provider-initiated counselling and testing (PICT) of children and disclosure of HIV status to children, including the following: lack of child-friendly infrastructure at clinics; lack of consensus on legal age of consent for both HIV testing and disclosure; healthcare worker unfamiliarity with HIV testing and disclosure guidelines; lack of training in child psychology; and confusion around the healthcare worker’s role, which most believed was only to provide health education and clinical services and to correct false information, but not to participate in disclosure. Additionally, primary caregivers were reported to be a barrier to care and treatment of children as they continue to refuse HIV testing for their children and delay disclosure. Conclusion. Training, mentoring, and providing healthcare workers with guidelines on how to provide child-focused HIV care have the potential to address the majority of the barriers to the provision of child-friendly HIV services to children. However, the need to educate primary caregivers on the importance of testing children and disclosing to them is equally important.